Biodegradable Polyurethane Solid-Solid Phase Change Materials - OKTAY, BURCU; KAYAMAN APOHAN, NİLHAN (WILEY-V C H VERLAG GMBH, 2021)
Polyurethane based phase change material (PCM) was prepared using polyethylene glycol (PEG), isophoronediisocyanate and octadecanol via a two-step process. PEG and octadecanol served as phase change components. The structural characterization of PCM was performed by ATR-FTIR and H-1-NMR spectroscopies. The latent heat, phase change temperature and thermal stability of PCM were characterized by differential scanning calorimetry and thermogravimetric analysis. The results show that PCM has an excellent energy storage capacity, suitable phase transition temperatures and great thermal stability at 100 degrees C without leakage. PEG/octadecanol polyurethane PCM reached 126 and 95 J/g enthalpy values. To investigate the efficiency of the PCM in a biodegradable polymeric support, blend films were prepared by mixing PEG/octadecanol polyurethane with the PLA. Films exhibited high light transmission. Elongation at break increased compared with pure PLA from 6 % to 87 %. In addition, tensile strength and modules of PLA/PEG-octadecanol PCM decreased. Water contact angle values of the films increased to 66 and 70 degrees with adding polyurethane PCM. In conclusion, PLA/PCMs exhibited high thermal energy storage property and suitable phase change temperature as good as the PEG/octadecanol polyurethane PCM. Therefore, PLA/PCMs can be used in ranges between 10 and 55 degrees C.
Keywords: Phase change material; polyurethane; polyethylene glycol; solid-solid PCM; THERMAL-ENERGY STORAGE; COMPOSITES; OIL; PEG